Fluidic oscillator with active phase control - Nicholls, CJ; Bacic, M (American Institute of Aeronautics and Astronautics, 2023)
This paper demonstrates the closed-loop control of the frequency and phase of a fluidic oscillator using acoustic excitation. It is shown experimentally that the use of acoustic excitation modifies the passive feedback mechanism and slows down the jet switching process. Closed-loop control is employed to vary the oscillation frequency at a fixed flow rate and track a sinusoidal reference target without phase error, using measurements from a pitot probe in the device. The controller is demonstrated to be effective at rejecting disturbances, which is illustrated with both time and frequency domain data. The controller’s ability to track step changes to the reference signal phase is tested and the closed-loop bandwidth is shown to be around 20% of the oscillation frequency, in close agreement with the theoretical prediction.